A nova economia institucional de Douglass North e seus reflexos no panorama dos direitos fundamentais brasileiros - Nunes, Rafael Domingos Acioly (2015)
The combination between two sciences; economics and law: then the New Institutional Economics appeard. The justification of this argument will be explained in two different parts. The first one explains the relation between jurists and economists. This part also hilights the differences and rivalries of its knowledge, participation in the Brazilian laws’ structure as well as the contruction of a stage that is, currently, prestigious by the economic knowledge. The second part deals with the details and phases of a specific economics science research. It also supports with theory, the recent reform in the legal institutions and brings back the knowledge that one day was manipulated only by jurists. In this sense, by the program above mentioned (NIE), lawyers can also take place in the highest positions in the economics market. From this heterodox formal division of the labor, it is possible to verify the aim of the law’s knowledge regarding to the need of its reformulation. So, it is wished to create a field for the theorical assumptions improvements, explain the globalised world complexities, revoke the lawyer’s thecnical competences in its field and in the State as a whole. As a tool for those proposals, the bibliographic methodology of Douglass North as well as the contribution of some jurists, have been used. The present study tries to demonstrate that NIE’s legitimacy impacts in the fundamental laws and in the jurists’ conditions to the Brazilian society – through multilateral organizations. From the sinergy of those two aspects, it can be revealed a great opportunity to improve those laws’ effectiveness as well as their legitimacies. The conclusion forms an argument that NIE, specially after the negotiations related to the Rule of Law and the informal institutions, serves more as an incentive to the jurists bring back their legitimacies than as a barrier for them.